2015
DOI: 10.1159/000381850
|View full text |Cite
|
Sign up to set email alerts
|

Management of Cytomegalovirus Seroconversion during Pregnancy in France

Abstract: Introduction: Guidelines for the management of cytomegalovirus (CMV) infection of the fetus are rare. Our main objective was to evaluate how health care practitioners in France manage cases of CMV seroconversion during pregnancy. Material and Methods: A questionnaire was e-mailed to health care practitioners potentially concerned by CMV seroconversion during pregnancy. They were asked if they would recommend amniocentesis, fetal cerebral MRI examination and fetal blood analysis (FBA), depending on the ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Our results are globally comparable with previously published studies about management process of pregnant women with CMV, including practice surveys [56] and literature reviews [57][58][59][60]. While amniocentesis and US examination are widely performed, approaches to FBS, MRI, and therapies are more diverse.…”
Section: Main Findingssupporting
confidence: 88%
See 2 more Smart Citations
“…Our results are globally comparable with previously published studies about management process of pregnant women with CMV, including practice surveys [56] and literature reviews [57][58][59][60]. While amniocentesis and US examination are widely performed, approaches to FBS, MRI, and therapies are more diverse.…”
Section: Main Findingssupporting
confidence: 88%
“…One common limitation in systematic review is the potential presence of publication bias which could in our case overestimate these interventions compared to real life practices. In 2016, Carrara et al [56] published management practices after CMV PI in pregnant women in France, from a survey of gynecologists' practices. Amniocentesis was performed in only 57% to 62% of cases after a PI in the first trimester of pregnancy without US abnormalities, compared to 91% in our study.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, based on our experience, routine screening can lead to unnecessary intervention, including unnecessary abortions [14]. On the contrary, in case of abnormal ultrasound suggestive of CMV, we believe that it could be useful to investigate the serological status of the mother, as recently proposed for primary infection in a review about the management of CMV seroconversion during pregnancy in France [25]. Non-primary maternal CMV infection can in fact be diagnosed during pregnancy, as detailed above.…”
Section: Discussionmentioning
confidence: 94%
“…In the absence of a vaccine against cytomegalovirus [6,14], some authors have suggested that screening during pregnancy or at birth could be good options to decrease the frequency of poor outcomes [15][16][17], but the possible benefits of screening has been debated [6,15,[18][19][20][21][22][23][24][25][26][27][28][29]. Diagnosis of a primary infection relies on the appearance of IgG, or a significant increase in IgG or presence of IgM; a test of IgG avidity can confirm the date of infection, with an uncertainty of 3 months [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%